Caracterização das variáveis limnológicas em quatro praias do rio Xingú, Altamira-PA - NASCIMENTO, Ana Caroline Leal (2022)
The Xingu River is a tributary of the Amazon basin and has variated uses, such as water supply, transport, energy generation, traditional communities’ subsistence, and recreation. Monitoring of limnological variables in aquatic ecosystems, such as rivers, is necessary to verify the conditions and functioning of an ecosystem. Especially in those environments that are influenced by urban areas and hydroelectric projects, as the Xingu River. Therefore, this study aimed to analyze and characterize the limnological variables in four beaches of the Xingu River in the Altamira-PA municipality. The study was conducted monthly from September 2018 to September 2019. Water Temperature (° C), Dissolved Oxygen (mg / L), pH, Electrical Conductivity (μS / cm) and Turbidity (NTU) were measured in the dry periods. and rainy. To verify the spatial variation between the variables an ANOVA (analysis of variance) was applied, showing that there were no differences in variances when comparing the locations and the periods. A T-test was also applied to verify if there are differences between the means of the variables in the dry and rainy periods. Water temperature showed differences in the dry season, pH and turbidity showed differences in the rainy season. To evaluate the correlations of the variables, Pearson's correlation was used, both overall and for each location. For each location the variables showed different correlations, although being the same river, these differences may be related to seasonality or other factors.